Assessment of Climate Change Impacts on Water Quantity and Quality at Small Scale Watersheds - Ouyang, Ying; Panda, Sudhanshu Sekhar; Feng, Gary (2022)
This book was inspired by the Hydrology-H030 Session of the 2019 AGU (America Geophysical Union) Fall Meeting. In recent years, simulating potential future vulnerability and sustainability of water resources due to climate change are mainly focused on global and regional scale watersheds by using climate change scenarios. These scenarios may have low resolution and may not be accurate for local watersheds. This book addresses the impacts of climate change upon water quantity and quality at small scale watersheds. Emphases are on climate-induced water resource vulnerabilities (e.g., flood, drought, groundwater depletion, evapotranspiration, and water pollution) and methodologies (e.g., computer modeling, field measurement, and management practice) employed to mitigation and adapt climate change impacts on water resources. Application implications to local water resource management are also discussed in this book.